EFFECT OF AEROBIC EXERCISE ON CARDIORESPIRATORY FUNCTIONS OF PRIMARY SCHOOL PUPILS IN IBADAN NORTH-EAST LOCAL GOVERNMENT AREA, OYO STATE, NIGERIA (2014)
Positive health and wellness across all ages have been associated with regular participation in aerobic activities. Studies have been carried out on aerobic exercise, but not much has been documented on the effect of this exercise on the cardiorespiratory functions of Nigerian children. Hence, this study investigates the effect of aerobic exercise on Forced Vital Capacity (FVC), Forced Expiratory Volume (FEV1), Peak Expiratory Flow Rate (PEFR), Resting Heart Rate (RHR), Resting Systolic Blood Pressure RSBP), Resting Diastolic Blood Pressure (RDBP) and Maximum oxygen uptake (VO2Max) among primary school pupils in Ibadan North East Area of Oyo State. Pretest-posttest control group experimental design was adopted. The purposive sampling technique was used to select 128 pupils from public and private schools in Ibadan. The participants were randomly assigned into experimental and control groups. The experimental group engaged in aerobic exercises such as brisk-walking, running on the spot, cycling in the air, rope-skipping, hopping and bench stepping activities while the control group did only flexibility exercises. The research instruments used were standard stadiometer, (r=0.99), weighing scale (r=0.99), computerised spirometer (r=0.99) and Mini Wright peak flow Meter (r=0.99). Three research questions were answered and six hypotheses tested at 0.05 level of significance. Mean, standard deviation, paired t-test and analysis of covariance were employed for data analysis. There was a significant difference between experimental and control groups in FVC (F(4,123)=3.122; P<0.05) and VO2max (F(4,123)=4.740, P<0.05). There were significant differences between public and private schools with FVC (t=2.09; df=127; P<0.05), FEV1 (t=10.06, df=127; P<0.05), PEFR (t=12.7; df=127; P<0.05), SBP (t=12.93; df=127; P<0.05), and HR (t=2.60; df=127; P<0.05). Significant sex differences were recorded on FVC (t=2.36; df=63; P<0.05), PEFR (t=4.26; df=63; P<0.05), SBP (t=5.40; df=63; P<0.05), and DBP (t=3.8; df=63; P<0.05). Though, the results imply that children have more tendencies for cardiorespiratory adaptation and improvement, private school pupils have better responses to exercise training than their counterparts in public schools. Furthermore, it is also significant when the participants were exposed along gender basis (P<0.05) with FVC of female (t=2.36; df=63; p<0.05) ( =1.53) better than the males counterparts ( =0.93). This implies that the female participants had better respiratory adaptations than their male counterparts during aerobic training. Aerobic exercise training has positive effects on cardiorespiratory functions. Therefore, professionals and stakeholders should ensure that children are well conditioned during training and also increase their physical activity levels for regular participation in aerobic activities to enhance positive health and wellness that reflects these cardiorespiratory indices (FVC, FEV1, PEFR, RHR, RSBP, RDBP& VO2max).